ANALISIS MODUS OPERANDI KECURANGAN PADA LAPORAN KEUANGAN JIWASRAYA PERIODE 2011-2021 - Naura, Refin Magiya; Kawedar, Warsito (Diponegoro Journal of Accounting, 2024)
Fraudulent practices in financial statements can have a big impact on the company, stakeholders, and public trust in the industry. Reliable reporting that is in accordance with real conditions is the basis for interested parties to make rational decisions. Due to the desire to maintain its position in a competitive market and public trust in its business, Jiwasraya's directors took steps that led Jiwasraya to default. Jiwasraya was able to report a rapid rate of revenue growth over several years that was matched by a sharp increase in debt. The modus operandi used by Jiwasraya's directors undermined public confidence in the insurance company and raised questions about the accounting practices of auditors and corporate governance norms in state-owned companies. The purpose of this research is to find out the modus operandi used by Jiwasraya management in the fraudulent practice of financial statement fraud. This research is a descriptive qualitative research with a case study approach with a sample of Jiwasraya's financial statements for 2011-2021 using horizontal analysis, vertical analysis, content analysis, and Altman Z-Score. The results of the study explain that the modus operandi used by Jiwasraya's management in committing fraud is to expand new business lines with offers of high returns, conduct investments without proper studies, present financial statements by utilising the momentum of window dressing, and report asset revaluations to engineer financial statements.